Metal cutting is it still of interest to anyone? - Veronica Banciu, Felicia; Pamintas, Eugen (Journal of Production Engineering, 2023)
For almost 100 years, the phenomena in the metal cutting process have offered researchers in the field a wide range of research topics, and at the same time, as much satisfaction, both in terms of deepening theoretical knowledge, especially in terms of the practical results obtained. Interest in this field has declined dramatically, however, since the beginning of the third millennium. Has the cutting process reached the limits of knowledge by their exhaustion or has it become inefficient for industry compared to other new processes for manufacturing metallic, non-metallic materials and composites? Why is the field no longer as attractive to researchers? Here is what this paper tries to clarify and propose to researchers in the field to reinvent the approach of the cutting process, as an incomplete explored and still excellent perspective, not only for the manufacturing industry, but also for the theoretical foundations of the cutting phenomenon.